2021
DOI: 10.1111/codi.15861
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta‐analysis of variants of the branches of the superior mesenteric artery: the Achilles heel of right hemicolectomy with complete mesocolic excision?

Abstract: Aim:Dissection with subsequent ligation and resection of arteries at their origin (central vascular ligation) is essential for adequate oncological resection during right hemicolectomy with complete mesocolic excision. This technique is technically demanding due to the highly variable arterial pattern of the right colon. Therefore, this study aims to provide a comprehensive evidence-based assessment of the arterial vascular anatomy of the right colon.Methods: A thorough systematic literature search through Sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
2
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 56 publications
1
10
2
2
Order By: Relevance
“…However, Spasojevic et al found that the ICA was absent in 2 out of 50 cases detected by multidetector CT angiography ( 10 ). Also, in Cirocchi et al ’s study, among 60 patients with malignant colonic cancer who underwent laparoscopic radical right colectomy and D3 lymph node dissection, there were 2 cases in which the ICA was absent, and the ICV was present in all 60 cases ( 11 ). Our paper is the first to report a case of two branches of the ICA originating from the SMA.…”
Section: Discussionmentioning
confidence: 96%
“…However, Spasojevic et al found that the ICA was absent in 2 out of 50 cases detected by multidetector CT angiography ( 10 ). Also, in Cirocchi et al ’s study, among 60 patients with malignant colonic cancer who underwent laparoscopic radical right colectomy and D3 lymph node dissection, there were 2 cases in which the ICA was absent, and the ICV was present in all 60 cases ( 11 ). Our paper is the first to report a case of two branches of the ICA originating from the SMA.…”
Section: Discussionmentioning
confidence: 96%
“…Many reports have described the anatomy of the ileocolic and right colic artery and vein. (4)(5)(6)(7)(8)(9)(10)(11)(12)(20)(21)(22) Moreover, the effect of lymph node dissection in right colectomy has been reported. (23,24) Surgery for transverse colon cancer is highly di cult because of the many variations of the MCA and SMV branches.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of ileocolic artery and right colic artery and vein variations (4)(5)(6)(7)(8)(9)(10)(11)(12) and accessary middle colic artery (13)(14)(15)(16)) has been reported, but few of studies have focused on the middle colic artery (MCA) (17,18) and no studies have focused on the relationship between the MCA and superior mesenteric vein (SMV). We considered that the relationship between the MCA and SMV has been very important in the case of lymph node dissection around the MCA.…”
Section: Introductionmentioning
confidence: 99%
“…The technique of colon cancer surgery has been completed and standardized since Hohenberger et al [8] proposed complete mesocolic excision (CME) by combining lymphatic drainage with mesocolic plane dissection, in which the embryological mesocolon, from the viscera to the parietal planes, is removed horizontally and the main artery pedicle is ligated at the root in the vertical direction. Recent studies showed that CME could eliminate tumour tissue by removing the entire relevant mesentery, thereby reducing local recurrence and improving survival significantly [9–13]. However, most studies regarding AC were performed at a time when CME was not proposed and generalized [14].…”
Section: Introductionmentioning
confidence: 99%
“…drainage with mesocolic plane dissection, in which the embryological mesocolon, from the viscera to the parietal planes, is removed horizontally and the main artery pedicle is ligated at the root in the vertical direction. Recent studies showed that CME could eliminate tumour tissue by removing the entire relevant mesentery, thereby reducing local recurrence and improving survival significantly [9][10][11][12][13].…”
mentioning
confidence: 99%